Management of releasable full denture in patient with pseudo jaw relation class III: a case report - Elvi Elvi; Edy Machmud; Bahruddin Thalib; Armawati Arafi; Indah Sulistiawaty (Journal of Dentomaxillofacial Science, 2017)
Objective: To give information about management of releasable full denture in patient with pseudo jaw relation class IIIMethods: A 58 years old woman came with complaints that she could not chew food and felt shy when she laughed, the woman asked a denture made for her. Last tooth withdrawal was 3 months ago. Shape of upper jaw sharp edge is triangle (pointed alveolar ridge), while lower jaw sharp edge is in resorbtion condition. Making of denture was started with initial molding, physiology molding, bite determination, and teeth arrangement based on Lingualized occlusion to insertion.Results: A case with pseudo jaw relation class III successfully treated using denture with lingualized occlusion.Conclusion: Teeth arrangement using occlusion pattern Lingualized occlusion can give natural appearance to patient and stability of denture.